An Audit of Influenza Vaccination Status in Adults with Inflammatory Bowel Disease - Neeraj Narula; Amit S Dhillon; Usha Chauhan; John K Marshall (Canadian Journal of Gastroenterology)
BACKGROUND Several guidelines recommend influenza vaccination for high-risk patients, including those on immune-suppressing medications (IS).